2009
DOI: 10.1177/1470320309347782
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II type 2 receptor gene polymorphisms in cardiovascular disease

Abstract: Considerable progress in our understanding of the role of the angiotensin II type 2 (AT 2 ) receptor in the development of cardiac hypertrophy and coronary artery disease has been achieved using in vitro and in vivo animal models. Our understanding in humans, however, has been hindered by the lack of availability of specific AT 2 receptor agonists and antagonists suitable for human study. Nevertheless, an alternative approach involving genotyping humans for a functional polymorphism within the AT 2 receptor ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Consequently, it has a protective influence on cardiovascular diseases [33]. At present, regardless of the molecular basis that determines this phenomenon, and conflicting data [34], it is believed that the A allele predisposes to the development of cardiovascular pathology [35][36][37]. The results of our study are entirely consistent with this concept: hemizygotes for the A allele are significantly more frequent among men with coronary artery disease than in the control group (OR 1.833; CI 1.046-3.214).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, it has a protective influence on cardiovascular diseases [33]. At present, regardless of the molecular basis that determines this phenomenon, and conflicting data [34], it is believed that the A allele predisposes to the development of cardiovascular pathology [35][36][37]. The results of our study are entirely consistent with this concept: hemizygotes for the A allele are significantly more frequent among men with coronary artery disease than in the control group (OR 1.833; CI 1.046-3.214).…”
Section: Discussionmentioning
confidence: 99%
“…This effect may be due to the fact that the AT2 receptor is expressed at low levels in normal tissues but upregulated in pathological states, including hypertension, vascular injury, myocardial infarction, stroke and heart failure. 23 …”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] This discrepancy might be explained by the vulnerability of association studies to the effect of confounding variables that influence the eventual cardiovascular phenotype, if these are not adjusted for in statistical analyses. 18 While the effect of this +1675 G/A polymorphism on hypertrophy in patients with HCM is unknown, Deinum et al 19 reported an association between a single nucleotide polymorphism (SNP) in the 3' untranslated region (UTR) of AGTR2, rs11091046, and left ventricular mass index (LVMI), observed only in female HCM patients. However, this study of ungenotyped cases did not account for differences in the primary HCM causal mutation, which may have had confounding effects on the association.…”
Section: Introductionmentioning
confidence: 99%